Evaluation of WarmStart Colorimetric Loop-Mediated Isothermal Amplification Assay for Diagnosis of Malaria - Lai, Meng Yee (American Society of Tropical Medicine and Hygiene, 2020)
The incidence of zoonotic malaria, Plasmodium knowlesi, infection is increasing and now is the major cause of malaria in Malaysia. Here, we describe a WarmStart colorimetric loop-mediated isothermal amplification (LAMP) assay for the detection of Plasmodium spp. The detection limit for this assay was 10 copies/mu L for P knowlesi and Plasmodium ovale and 1 copy/mu L for Plasmodium falciparum, Plasmodium vivax, and Plasmodium malariae. To test clinical sensitivity and specificity, 100 microscopy-positive and 20 malaria-negative samples were used. The WarmStart colorimetric LAMP was 98% sensitive and 100% specific. Amplification products were visible for direct observation, thereby eliminating the need for post-amplification processing steps. Therefore, WarmStart colorimetric LAMP is suitable for use in resource-limited settings.